Ramification of hustling the web application development - Kaur, Daljit; Parminder Kaur, Dr (International Journal of Engineering and Technology, 2018)
With the growth of web and Internet, every era of human life has been affected. People want to make their or their organization’s presence globally visible through this medium. Web applications and/or mobile apps are used for the purpose of making their recognition as well as to attract the clients worldwide. With the demand of putting the business or services online faster than anyone else, web applications are developed in hustle and under pressure by developers and most of the times they ignore the few essential activities for securing them from severe attacks, which may be a greater loss for the business. This work is an effort to understand the complex distributed environment of web applications and show the impact of husting the web development process.